Ankylosing hyperostosis: a study of HLA A, B, and C antigens. Issue 1 (February 1979) - Perry, J D; Wolf, H; Festenstein, H; Storey, G O
Abstract : HLA A, B, and C antigens were studied in 25 patients with ankylosing hyperostosis. There was no evidence of an increased frequency of any antigen in association with the condition itself. However, a high frequency of several antigens was found, reflecting the predominance of Jewish patients in the series.